(untitled) (Bangladesh Journal of Neuroscience, 2017)
We would like to report on a patient, a 52-year-old man with acute neurologic disorder, Guillain Barré Syndrome. He was successfully treated by intravenous immunoglobulin. The patient suffered from acute extensive anterior MI. 2 weeks after thrombolytic therapy with streptokinase, he developed GBS. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 103-104